2010
DOI: 10.1002/hed.21506
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after the use of gastrostomy tubes in patients whose head and neck cancer was managed with radiation therapy

Abstract: The beneficial effects of continued oral intake and shorter gastrostomy tube placement on posttreatment outcomes shown in this study suggest that clinicians involved in these patients' care should emphasize oral intake during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…1 Although smoking and tobacco use remain primary risk factors, human papillomavirus malignancies especially in the oropharynx are on the rise. 1,3 In particular, swallowing dysfunction, whether pre treatment or post treatment, [4][5][6][7] contributes significantly to both morbidity and mortality especially in older adults. 1,3 In particular, swallowing dysfunction, whether pre treatment or post treatment, [4][5][6][7] contributes significantly to both morbidity and mortality especially in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although smoking and tobacco use remain primary risk factors, human papillomavirus malignancies especially in the oropharynx are on the rise. 1,3 In particular, swallowing dysfunction, whether pre treatment or post treatment, [4][5][6][7] contributes significantly to both morbidity and mortality especially in older adults. 1,3 In particular, swallowing dysfunction, whether pre treatment or post treatment, [4][5][6][7] contributes significantly to both morbidity and mortality especially in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrostomy dependence was less likely for patients receiving higher quality care, but higher quality care was not associated with differences in survival in patients with gastrostomy dependence. [16][17][18][19][20][21][22][23][24] In addition to chemotherapy, there is a known relationship between radiation dose and the extent of short-term and longterm soft tissue toxicity, with doses >60 Gy associated with an increased risk of late dysphagia and gastrostomy use. In elderly patients with OPSCC, we found no significant association between high-quality care and the likelihood of dysphagia and gastrostomy dependence, but higher quality care was associated with improved survival in patients with dysphagia or gastrostomy dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic feeding tube placement has been recommended at some institutions to diminish the risk of hospitalization for mucositis‐induced dehydration and/or aspiration, to support nutrition, and improve quality of life during treatment . Prophylactic placement may, however, be associated with prolonged feeding tube dependence and possibly worse long‐term swallowing outcomes . Recent studies have shown that approximately half of the patients undergoing chemoradiation may not require a gastrostomy …”
Section: Discussionmentioning
confidence: 99%
“…The insertion of a feeding tube prophylactically before the initiation of treatment has been shown to decrease weight loss and the rate of hospitalization during chemoradiation . However, prolonged feeding tube dependence and worse long‐term swallowing outcomes in patients undergoing prophylactic gastrostomies have been reported . These observations may be a consequence of preexisting dysphagia, rather than prophylactic gastrostomy placement per se.…”
Section: Introductionmentioning
confidence: 99%